1977
DOI: 10.1152/jappl.1977.43.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory and cholinergic control of pulmonary surfactant in the rabbit

Abstract: Four sets of experiments on surfactant secretion were performed using New Zealand rabbits under light pentobarbital anesthesia. Pa02, Paco2, and pHa remained normal during all experiments. In controls lung lavage yielded 1.62 +/- 0.26 (SD) mg of alveolar phospholipid (PL)/g lung; disaturated phosphatidylcholine comprised 55.5% of total PL. a) Acetylcholine infusion into the left pulmonary artery for 1-4 h caused a 13% increase in alveolar PL of left as compared to right lung. b) Efferent left vagus stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(36 citation statements)
references
References 0 publications
1
34
1
Order By: Relevance
“…Smith (28) has shown that cultured cells similar to type I1 alveolar cells secrete increased amounts of phosphatidylcholine in response to acetylcholine and this effect may be blocked by atropine. In adult rabbits, increased pulmonary ventilation leads to increased alveolar Surfactant and this effect is mediated at least partially by the vagus nerve (23). In the present experiments, atropine blocked the effect of gas ventilation on net accumulation of alveolar surfactant after birth.…”
Section: Atropine O 3 U S I O N Me-rwrmentsupporting
confidence: 53%
“…Smith (28) has shown that cultured cells similar to type I1 alveolar cells secrete increased amounts of phosphatidylcholine in response to acetylcholine and this effect may be blocked by atropine. In adult rabbits, increased pulmonary ventilation leads to increased alveolar Surfactant and this effect is mediated at least partially by the vagus nerve (23). In the present experiments, atropine blocked the effect of gas ventilation on net accumulation of alveolar surfactant after birth.…”
Section: Atropine O 3 U S I O N Me-rwrmentsupporting
confidence: 53%
“…Ventilation was assisted in four of five HMD animals and has been reported to increase PL recovered in airways lavage (21). However, this effect of ventilation is much too d l to account for the differences described here in PL in whole lung and SAM between normal and HMD lungs.…”
Section: Discussionmentioning
confidence: 64%
“…Decreased compliance after periods up to 4 h of increased ventilation were attributed to altered surfactant function because extracts from these lungs exhibited increased minimal surface tensions (6)(7)(8)(9)(10). Increased alveolar surfactant phospholipids were found by Oyarzun and Clements (8, 9) after hyperventilation of adult rabbits for periods up to 4 h. They postulated that increased secretion of tissue pools occurred followed by inactivation.…”
Section: Resultsmentioning
confidence: 99%
“…Oyarzun and Clements (8, 9) measured alveolar surfactant phospholipids in hyperventilated adult rabbits and found that alveolar surfactant increased during the first 2 h but substantially decreased after 4 h of increased tidal volume ventilation. They speculated that secretion was stimulated by hyperventilation, thereby increasing alveolar surfactant pools at the expense of tissue pools (8,9). Similar conclusions were drawn by Wyszogrodski et al from their study of hyperventilated adult cats (10).…”
Section: Perinatal Research Laboratories Department Of Pediatrics Hmentioning
confidence: 99%